IMAGES OF MOTHERHOOD IN BUKUSU WORK AND CELEBRATORY SONGS - George Wanjala, Kasili; Kabaji, Prof. Egara; Omuteche, Dr. Jairus (IJRDO - Journal of Social Science and Humanities Research, 2016)
This paper is a reading of the different images that the person of mother is associated with among the Babukusu community through the performance of their work and celebratory songs. Motherhood in the paper refers to the Bukusu understanding of the person of mother. The paper is of the view that the mother in the community occupies some gendered space(s) as opposed to the patriacally demarcated inferior position. The space(s) she occupies are/is evident in the different images constructed of her in the selected songs. The paper benefits from an intra-communal comparison of the images created during a masculine occasion (initiation) and feminine occasions (twin dances and white ants tapping).Being a true parent, nurturer/caretaker, proactive, hardy/an impenetrenable rock and a complement of the father are the spaces that define her in the community.